A real‐time PCR assay for improved rapid, specific detection of Cryphonectria parasitica. (7th April 2017) - Rubio, S.; Barnes, A.; Webb, K.; Hodgetts, J.
ABSTRACT: Cryphonectria parasitica, an ascomycete fungus, is the causal agent of chestnut blight. This highly destructive disease of chestnut trees causes significant losses, and is therefore a regulated pathogen in Europe. Existing methods for the detection of C. parasitica include morphological identification following culturing, or PCR; however, these are time‐consuming resulting in delays to diagnosis. To allow improved detection, a new specific real‐time PCR assay was designed to detect C. parasitica directly from plant material and fungal cultures, and was validated according to the European Plant Protection Organisation (EPPO) standard PM 7/98. The analytical specificity of the assay was tested extensively using a panel of species taxonomically closely related to Cryphonectria, fungal species associated with the hosts and healthy plant material. The assay was found to be specific to C. parasitica, whilst the analytical sensitivity of the assay was established as 2 pg µL −1 of DNA. Comparative testing of 63 samples of naturally infected plant material by the newly developed assay and traditional morphological diagnosis demonstrated an increased diagnostic sensitivity when using the real‐time PCR assay. Furthermore the assay is able to detect both virulent and hypovirulent strains of C. parasitica . Therefore the new real‐time PCR assay can be used to provide reliable, rapid, specific detection of C. parasitica to prevent the accidental movement of the disease and to monitor its spread.